Value-added processing of crude glycerol into chemicals and polymers. (September 2016) - Luo, Xiaolan; Ge, Xumeng; Cui, Shaoqing; Li, Yebo
Highlights: Crude glycerol components vary with the feedstock and biodiesel production methods. Routes for direct conversion of crude glycerol to high-value products are reviewed. Low product yield and productivity and impacts of impurities are major issues. Low production issues may be addressed by techniques developed with pure glycerol. Strategies for addressing the impurity issues are discussed. Abstract: Crude glycerol is a low-value byproduct which is primarily obtained from the biodiesel production process. Its composition is significantly different from that of pure glycerol. Crude glycerol usually contains various impurities, such as water, methanol, soap, fatty acids, and fatty acid methyl esters. Considerable efforts have been devoted to finding applications for converting crude glycerol into high-value products, such as biofuels, chemicals, polymers, and animal feed, to improve the economic viability of the biodiesel industry and overcome environmental challenges associated with crude glycerol disposal. This article reviews recent advances of biological and chemical technologies for value-added processing of crude glycerol into chemicals and polymers, and provides strategies for addressing production challenges.